A case of Undifferentiated connective tissue disease - Chatterjee, A; Chatterjee, K; Sarkar, N (Journal of College of Medical Sciences-Nepal, 2014)
Undifferentiated connective tissue disease is an overlap syndrome in which the features of more than one disease is present but their complete diagnosis is lacking. We are presenting an 11year child with fever, arthritis, polyserositis, myalgia, nephritis, sclerodactyly with positive anti-dsDNA and anti-Smith antibody. She improved with prednisolone and cyclophosphamide. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 59-62 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10238